2013
DOI: 10.3329/jom.v14i1.14533
|View full text |Cite
|
Sign up to set email alerts
|

Association of Biofilm Formation with Antimicrobial Resistance Among the Acinetobacter Species in A Tertiary Care Hospital in Bangladesh

Abstract: Purpose: The purpose of this study was to detect biofilm formation in clinical isolates of Acinetobacter species and to observe correlation between biofilm formation and antimicrobial resistance among Acinetobacter isolates. Methods: Two hundred fifty six clinical samples collected from patients who were admitted in Intensive Care Unit (ICU) and on device, patients from Surgery, Medicine, Gynae & Obs and Urology department of Bangabandhu Sheikh Mujib Medical University (BSMMU) and from Burn unit of Dhaka M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…They found 100 % resistance to Amoxicillin, Ceftriaxone, Ceftazidime, Cefuroxime and Aztreonam in biofilm-forming Acinetobacter species. This results is parallel to ours [51]. They showed that the presence of biofilm in addition to the gelatinase and hemagglutination characteristics may play a role in the pathogenesis of A. baumanniibacteria.…”
Section: Discussionsupporting
confidence: 89%
“…They found 100 % resistance to Amoxicillin, Ceftriaxone, Ceftazidime, Cefuroxime and Aztreonam in biofilm-forming Acinetobacter species. This results is parallel to ours [51]. They showed that the presence of biofilm in addition to the gelatinase and hemagglutination characteristics may play a role in the pathogenesis of A. baumanniibacteria.…”
Section: Discussionsupporting
confidence: 89%
“…To avoid errors related to measurement uncertainty, and to allow comparison of results obtained by different laboratories or methods, Stepanović et al proposed a categorization method for biofilm formation based on the absorbance of control wells: ‘cutoff’ OD + 3 SD of this absorbance. This categorization, although originally developed for staphylococci, has previously been used successfully to assess biofilm formation by A. baumannii . The calculated cutoff value is strongly related to the repeatability and precision of the assay, and in cases where the standard deviation of the blank well ODs is low, more strains will be classified as forming a biofilm than in cases where the variance is higher.…”
Section: Discussionmentioning
confidence: 99%
“…Nahar et al found that all biofilm‐producing Acinetobacter isolates were resistant to ceftazidime. In our study, this drug had one of the highest rates of resistance, with all moderate and strong biofilm producers resistant to ceftazidime.…”
Section: Discussionmentioning
confidence: 99%
“…isolates were reported as MDR and biofilm producers, especially those isolated from ICU samples. 155 More than 86% of the isolates from a tertiary care hospital in Mexico were resistant to ciprofloxacin, ceftazidime, and cefotaxime, and 50.7% and 35.5% of the isolates were resistant to imipenem and meropenem, respectively. 156 Of these isolates, 28.3% and 25.7% were positive for the bla OXA-58 and bla OXA-72 genes, respectively.…”
Section: Antibiotic Resistance and The A Baumannii mentioning
confidence: 99%